2006
DOI: 10.1016/j.febslet.2006.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Truncated tau from sporadic Alzheimer's disease suffices to drive neurofibrillary degeneration in vivo

Abstract: Truncated tau protein is the characteristic feature of human sporadic Alzheimer's disease. We have identified truncated tau proteins conformationally different from normal healthy tau. Subpopulations of these structurally different tau species promoted abnormal microtubule assembly in vitro suggesting toxic gain of function. To validate pathological activity in vivo we expressed active form of human truncated tau protein as transgene, in the rat brain. Its neuronal expression led to the development of the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
203
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(215 citation statements)
references
References 31 publications
9
203
0
2
Order By: Relevance
“…When truncated at the N terminus, tau cannot form filaments in cellfree systems, but may do so in vivo, and has been implicated in NFT formation and neurodegeneration (35,36). Given the granular appearance of the aggregates, another potential structural candidate for these aggregates are tau oligomers, which are monomeric or dimeric accumulations of highly phosphorylated or truncated tau (37,38). Tau oligomers have been detected in tau transgenic mice and in presymptomatic AD (1,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…When truncated at the N terminus, tau cannot form filaments in cellfree systems, but may do so in vivo, and has been implicated in NFT formation and neurodegeneration (35,36). Given the granular appearance of the aggregates, another potential structural candidate for these aggregates are tau oligomers, which are monomeric or dimeric accumulations of highly phosphorylated or truncated tau (37,38). Tau oligomers have been detected in tau transgenic mice and in presymptomatic AD (1,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on truncated t protein, which has been shown to be a driving force behind neurofibrillary degeneration in transgenic rats expressing misfolded truncated t (44,45). We have previously demonstrated that in the transgenic rat brain, neurofibrillary lesions and axonal degeneration are closely associated with the distribution of reactive microglia and macrophages (40).…”
Section: Human Truncated T Stimulates Activation Of Microglia Throughmentioning
confidence: 99%
“…N-terminal truncated, MtBr containing, tau fragments exhibit an increased tendency to aggregate. 88,89 MtBr-fragments are readily secreted and may induce calpain 84 /caspase 85 activation in recipient neurons increased resulting in self-regenerating tau lesion propagation. (C) tau/PrP interactions in exosomal secretion.…”
Section: Discussionmentioning
confidence: 99%